Gauging Households’ Debt Tolerance: Evidence from Thailand - Muthitacharoen, Athiphat (Asian Journal of Applied Economics, 2016)
Understanding households’ debt tolerance has direct implications on policies addressing high household debt in many Asian economies. This study examines the determinants of debt tolerance and assesses the tolerance level among different household segments. It defines the debt tolerance as the ability to cope with debt without suffering from anxiety and provides empirical evidence based on a survey on Thai households in 2013. Using the IV probit model, the findings indicate that factors important to the debt tolerance include debt burden and financial cushion as well as income security, financial history, and financial discipline. Given this range of factors, a multi-faceted approach is required to address the debt tolerance issue. The study highlights the relatively low debt tolerance among households in precarious jobs including farmers, general workers and business owners. The results are robust to a number of alternative specifications.